2001
DOI: 10.1542/peds.108.5.e79
|View full text |Cite
|
Sign up to set email alerts
|

Severe Complications of Varicella in Previously Healthy Children in Germany: A 1-Year Survey

Abstract: Objective. Varicella is a common infectious disease, usually benign and self-limited, and complications are believed to be rare. The purpose of this study was to describe the epidemiology of severe varicella complications in immunologically healthy children in Germany. Methods. Information on any admission of children with a severe complication associated with chickenpox was solicited throughout 1997 from all 485 pediatric ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(8 citation statements)
references
References 15 publications
0
5
0
3
Order By: Relevance
“…According to a prospective study, the most common complications reported in previously healthy children include encephalitis, osteomyelitis, and pyogenic arthritis. Infectious complications are lower in proportion but significantly contribute to the chronic sequelae and therefore require utmost care and management 3 …”
Section: Discussionmentioning
confidence: 99%
“…According to a prospective study, the most common complications reported in previously healthy children include encephalitis, osteomyelitis, and pyogenic arthritis. Infectious complications are lower in proportion but significantly contribute to the chronic sequelae and therefore require utmost care and management 3 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Also, severe complications could potentially lead to long-term sequelae such as persisting motion deficits (hemiparesis, nerve palsy, convulsion), scarring, bone and joint defects after infectious complications. 58 , 67 Only few studies reported on costs related to long-term disability and further studies are needed to evaluate the burden of varicella-related sequelae. 19 , 25 , 29 , 45 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Enfeksiyöz komplikasyonlar 4 yaş altındaki çocuklarda, nörolojik komplikasyonlar ise daha büyük çocuklarda sık izlenmiştir. Trombositopeni ve ciddi anemi 5/119 hastada saptanmıştır (10). Çalışmamızda hematolojik tutuluma bağlı komplikasyon olarak dört hastada nötropeni ve iki hastada trombositopeni saptanmıştır.…”
Section: Discussionunclassified